Interstitial cell of Cajal‐like cells in the upper urinary tract - Lang, R.J. (J Cell Mol Med, 2007)
Autorhythmicity in the upper urinary tract (UUT) has long been considered to arise in specialized atypical smooth muscle cells (SMC) predominately situated in the most proximal regions of the pyeloureteric system. These atypical SMC pacemakers have been thought to trigger adjacent electrically‐quiescent typical SMC to fire action potentials which allow an influx of Ca(2+) and the generation of muscle contraction. More recently, the presence of cells with many of the morphological, electrical and immunohistochemical characteristics of interstitial cells of Cajal (ICC), the pacemaker cells of the gastrointestinal tract, have been located in many regions of both the upper and lower urinary tract. This article reviews the evidence from the literature and from our laboratory supporting a role of both of both atypical SMC and ICC‐like cells in the initiation and propagation of pyeloureteric peristalsis in the UUT. We propose a new model in which there are 2 populations of pacemaker cells, high frequency atypical SMC and lower frequency ICC‐like cells, both of which can drive electrically‐quiescent typical SMC. The relative presence of these 2 populations of pacemaker cells and the relatively‐long refractoriness of typical SMC determines the decreasing frequency of contraction with distance from the renal fornix. In the absence of the proximal pacemaker drive from atypical SMC after pyeloureteral/ureteral obstruction or surgery, ICC‐like cell pacemaking provides a compensatory mechanism allowing the ureter to maintain rudimentary peristaltic waves and movement of urine from the pyelon towards the bladder.